1992
DOI: 10.1128/mcb.12.2.836
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase containing SH2 domains: characterization, preferential expression in hematopoietic cells, and localization to human chromosome 12p12-p13.

Abstract: The growth and many functional responses of hematopoietic cells are regulated through phosphorylation of proteins on tyrosine. However, most hematopoietic growth factor receptors and antigen receptors do not contain intrinsic protein kinase activity but nevertheless rapidly induce protein tyrosine phosphorylation (22-24, 31, 40, 42, 48). A variety of observations indicate that these phosphorylations are essential for a mitogenic response. In particular, introduction of protein tyrosine kinases has been shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
165
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(170 citation statements)
references
References 88 publications
(70 reference statements)
5
165
0
Order By: Relevance
“…Sequencing analysis of the cDNA fragment revealed that the coding region sequence is identical to the previously reported human SHP-1 cDNA sequence 13 (data not shown), indicating that the SHP-1 protein of the patient did not have point mutations. In support of this, we found that immunoprecipitated SHP-1 from the patient and the parents had comparable PTPase activities in in vitro PTPase assays (data not shown).…”
Section: Pbmc Of Fhlh Patients Express Normal Levels Of Functional Shsupporting
confidence: 70%
See 1 more Smart Citation
“…Sequencing analysis of the cDNA fragment revealed that the coding region sequence is identical to the previously reported human SHP-1 cDNA sequence 13 (data not shown), indicating that the SHP-1 protein of the patient did not have point mutations. In support of this, we found that immunoprecipitated SHP-1 from the patient and the parents had comparable PTPase activities in in vitro PTPase assays (data not shown).…”
Section: Pbmc Of Fhlh Patients Express Normal Levels Of Functional Shsupporting
confidence: 70%
“…1,9 Since the motheaten disease is associated with loss of functional hematopoietic cell phosphatase (SHP-1) due to mutations in the SHP-1 gene, 9,10 the clinical and histologic similarities between FHLH and the motheaten disease suggest a potential association of FHLH with abnormalities in SHP-1. 9 SHP-1 11 is a cytoplasmic protein tyrosine phosphatase predominantly expressed in cells of the hematopoietic system 12,13 and is also termed PTP1C, 14 SHPTP1, 15 SHP. 16 It has two srchomology 2 (SH2) domains at the amino region and a PTPase domain at the carboxyl terminal region.…”
Section: Introductionmentioning
confidence: 99%
“…Src homology region 2 domain-containing phosphatase 1 (SHP-1) is a non-transmembrane protein tyrosine phosphatase that is expressed predominantly in hemopoietic cells of all lineages and all stages of maturation as well as at lower levels in epithelial cells (21)(22)(23)(24)(25). The existence of a murine genetic model for SHP-1 deficiency has significantly aided our understanding of the biological function of SHP-1 (26,27).…”
Section: Deficiency Of the Src Homology Region 2 Domain-containing Phmentioning
confidence: 99%
“…SHP-1 (also named SHPTP-1, SHP, or HCP) is a non-transmembrane PTPase that contains two Src homology 2 (SH2) domains involved in its association with multiple signaling molecules (17)(18)(19)(20). SHP-1 associates in vivo with activated growth factor tyrosine kinase receptors such as epidermal growth factor receptor (21).…”
mentioning
confidence: 99%